Peningkatan Keterampilan Klinik Melalui Penerapan Mini-CEX pada Mahasiswa Keperawatan - Siska Evi Martina; Eva Hotmaria Simanjuntak (Faletehan Health Journal, 2020)
Lack of nursing competencies in Indonesia is still happened. The university or nursing high school who provided nursing education is one who responsible on this situation. Nursing skill should be achieved by nursing student to improve clinical skills. Mini-CEX is one of method which can be improve nursing student’s skilss. Objective of this study to identify effectiveness of mini-CEX on improvement nursing student’s clinical skills. Quasi experiment was conducted to reach 49 nursing student divide to 25 student as an intevention group and 24 student as a control group by total sampling. Mini-CEX form was applied to measure clinical skill. This study found that nursing student’s clinical skills before and after intervention was signficant different with pvalue =0.000 (< 0.05). After student getting feedback, they were improve their skills (Mean=35.24), this showed that significant different from before intervention (Mean= 25.56). Therefore, Mini-CEX is a great clinical evaluation method to encourage and help student for improving their clinical skills. Mini-CEX should be applied contuniously in hospital.